Differences in Bait Types on Mangrove Crab (Scylla Serrata) Catches Using Folding Trap in Pangkal Babu Village. - Sa'adah, Shopiyatus; Magwa, Rizky Janatul; Filawati, Filawati (Jurnal Media Akuakultur Indonesia, 2025)
Folding bubu fishing gear is one of the fishing gear operated to catch mangrove crabs in Pangkal Babu Village, catching mangrove crabs (Scylla serrata) using folding bubu fishing gear requires bait in an effort to increase catches effectively. This study aims to determine the difference in mangrove crab catches using stingray and tobul fish bait using folding bubu. This research was conducted in Pangkal Babu Village, Tanjung Jabung Barat on March 7 - April 7, 2024. The method used was experimental fishing. Data collected include the number, weight and width of mangrove crab catches, the number, weight, and width of the carapace of the catches are tabulated in the form of tables and graphs. The results showed that the number of mangrove crab catches was 27 with an average total weight of 407.8 g and an average carapace width of 198.4 mm. While the catch of mangrove crabs with tobacco fish treatment got 34 fish with an average weight of 602.4 g, and an average width of 267.6 mm. The results of the T test analysis showed that the bait type treatment had no significant effect (P> 0.05) on the number of mangrove crab catches, but had a significant effect (P < 0.05) on the weight and width of the mangrove crab carapace, From this study, it can be concluded that the use of tobacco fish bait in folding bubu fishing gear in Pangkal Babu Village resulted in higher carapace weight and width compared to the use of stingray bait.